Psychosocial Assistance For Patients' Families In Dealing With Cardiovascular Emergencies: Training And Simulation For Health Workers - Sari, Sofiani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Cardiovascular emergencies are the leading cause of death globally and have a major impact on patients and their families' psychosocial well-being. Families often experience anxiety, emotional stress and uncertainty in emergency situations, making psychosocial support an important aspect in supporting better medical decision-making. However, many health workers lack the skills to provide effective psychosocial support. This training aims to improve the understanding and skills of health workers through education and clinical simulation. The methods used included a needs survey, educational sessions, clinical simulations to practice empathic communication, and pre-test and post-test evaluations to measure the effectiveness of the training. The results showed a significant increase in health workers' understanding of psychosocial assistance, with an average improvement of 30-38% on various indicators. As many as 85% of participants found the training very useful, while 80% stated that the simulation provided an experience close to real conditions. The simulation-based approach proved to be more effective than theory alone because it provided direct experience in dealing with critical situations. In conclusion, psychosocial training and simulation can improve the competence of health workers in providing emotional and psychological support for patients' families. Continuous implementation of this program is expected to improve the quality of holistic health services, reduce family anxiety, and strengthen the humanistic approach in medical emergencies.